Respons Pertumbuhan Bibit Kelapa Sawit pada Media Tanam Kompos Limbah Organik Perkebunan - Madusari, Sylvia; Irma Sari, Vira; Jumardin; Hardianto, Sri; Pirnado Lubis, Bintang (Jurnal Galung Tropika, 2024)
The underutilization of oil palm midrib and fruit fiber, which are abundant in oil palm plantations and the manufacturing field, encourages them to be converted into more valuable products. The goals of this experiment were to create planting media out of oil palm midrib and fiber, as well as to find the best compost formulation of oil palm midrib (MR) and fiber (FF) for seedlings in prenursery. The treatments were arranged in a non-factorial completed randomized design, with 15 treatments. The treatments are  : P0 (100% top soil), P1 (50% MR + 50% CW + Activator 1), P2 (50% MR + 50% CW + Activator II), P3 (50% MR + 50% CW + POME); P4 (100% MR + Activator II); P5 (100% MR + LCPKS), M1 (50% FF : 50% CW + Activator 1); M2 (50%  FF : 50% CW + Activator II); M3 (50%  FF : 50% CW + POME); M4 (100%  FF + Activator II); M5 (100%  FF + POME), PM1 (50% MR-FF + 50% CW + Activator I); PM2 (MR-FF + 50% CW + POME); PM4 (100% MR-FF + Activator II); PM5 (100% MR-FF + POME). The results showed that oil palm midrib and fiber composting media significantly affected morphological responses of oil palm seed growth (plant height, stem diameter and leaf area seedlings), and physiological responses of oil palm seed growth (biomass and stomata conductance). These results could be promoted as a new challenge to formulating the lignocellulose-based planting media.